(untitled) (Journal of the College of Basic Education, 2025)
This research aims at recognizing the following: Level of “Persuasive writing” among the students of Arabic language departments at the Collages of Education. Variations in “Persuasive writing” due to different social gender (male vs female) The researcher applied the Descriptive Approach procedures, being the most applicable to achieve the research goal, she also restricted the research community to the students of Arabic Language Departments in the Collages of Education (the morning shift). The researcher chose 100 students (male and female) to be the sample of her research, and they were taken from among the first-year students in Arabic Language Department/Ibn Rushd Collage of Education– for Humanities. She arranged a skill test in “Persuasive writing” constituted of( 15) questions, after defining the appropriate skills in the light of a questionnaire that encompassed all those skills, by referring to previous literature and studies then put them before experts and specialized people in Arabic Language teaching methods, then its Psychometric specifications were concluded, and the test was applied on the research sample, then the appropriate statistical tools were served to “SPSS” program to work on. Accordingly, the researcher concluded the following results: 1.Weakness in “Persuasive writing” was prevailing among students of Arabic Language Department/Ibn Rushd Collage of Education . 2.There had been no variations in “Persuasive writing” due to the difference in social gender (male vs female)